Lymphocyte count and A-DROP score in COVID-19 patients: A retrospective observational study - Chandrakant Waikar; Vinayak Gour; Lal Pranay; Sevras Hingwe (Journal of Acute Disease, 2022)
Objectives: To determine the correlation between lymphocyte count and A-DROP score in COVID-19 patients and their role in predicting poor outcomes. Methods: This retrospective observational single-center study was conducted in a tertiary care hospital in Vidisha district, India. COVID-19 patients were included in this study, who were admitted to ICU and the COVID Care Centre from August 2020 to October 2020. Demographic profile, clinical characteristics, medical history, A-DROP score, complete blood counts including lymphocyte counts (on admission), the severity of the disease course, and duration of hospitalization were collected. The correlation between lymphopenia and A-DROP score was determined, and their role in predicting poor outcomes was investigated. Results: This study included 220 patients, among which 134 were male, and 86 were female [mean age (48.98±16.98) years, 95% CI: 46.72-51.23]. Lymphocyte count in COVID-19 patients negatively correlated with the A-DROP score (r=−0.67, P<0.001). The area under the ROC curve was 0.892 (95% CI: 0.80-0.98, P<0.001) for the lymphocyte count, and the area under the ROC curve was 0.93 (95% CI: 0.84-1.00, P<0.001) for lymphocyte count-A-DROP. Conclusion: Lymphocyte count along with the A-DROP score on admission could be used to predict the severity of COVID-19 pneumonia and unfavorable outcome.